Feeding and swallowing outcomes of children receiving long-term ventilation: A scoping review protocol. - Sabrena Lee; Jeanne Marshall; Michael Clarke; Christina H Smith (PLoS ONE, 2024)
Background The last three decades have seen a growth in the number of children requiring long-term ventilation. Children with long-term ventilation present with underlying respiratory and neurological conditions that place them at risk of feeding and swallowing difficulties. To date, a scoping review or systematic review investigating the feeding and swallowing outcomes of children with long-term ventilation needs has not been conducted. Aims This paper describes a protocol for a scoping review of the feeding and swallowing outcomes of children receiving long-term ventilation. Methods This scoping review protocol will utilize the Joanna Briggs Institute scoping review methodology guideline. Our review will focus on the feeding and swallowing outcomes of children aged 0 to 18 years with long-term ventilation needs. A full search strategy initially created by the authors and a research librarian was conducted on the PubMed database. Following this, pilot testing took place to determine discrepancies in eligibility criteria. A full search strategy will be conducted across several databases. A data extraction form has been developed by the authors and will be used during the scoping review process. Discussion This protocol has been created to provide a rigorous and comprehensive basis for undertaking a scoping review. All necessary steps have been completed in order to commence the scoping review. Registration This scoping review protocol was registered on Open Science Framework on the 26th November 2021 (Registration DOI 10.17605/OSF.IO/NQBPD).